LB16. Surveillance Rates of Cefiderocol Heteroresistance Correlate With All-cause Mortality in the APEKS-NP and CREDIBLE-CR Trials. (4th December 2021) - Choby, Jacob E; Ozturk, Tugba; Satola, Sarah W; Jacob, Jesse T; Weiss, David
Abstract: Background: Cefiderocol is a recently FDA approved, novel siderophore beta-lactam antibiotic. Conventional antimicrobial susceptibility testing (AST) suggests that a variety of Gram-negative pathogens, including carbapenem-resistant (CR) isolates, are overwhelmingly susceptible to cefiderocol.. This antibiotic performed well in the APEKS-NP trial for the treatment of nosocomial pneumonia caused largely by carbapenem susceptible isolates. However, in the CREDIBLE-CR trial involving exclusively CR Gram-negative bacteria, cefiderocol was associated with a higher rate of all-cause mortality. We hypothesized one explanation for these discrepant data might be undetected cefiderocol heteroresistance (HR). HR is a form of antibiotic resistance in which an isolate harbors a minority resistant subpopulation of cells co-existing with a majority susceptible population, and is often undetected by standard AST. Isolates exhibiting undetected HR, with as low as 1 in 1 million resistant cells, can cause treatment failure in in vivo models. Methods: We quantified HR to cefiderocol by population analysis profile (PAP) of 161 Acinetobacter, 180 Klebsiella, and 108 Pseudomonas isolates collected in Georgia, USA. Results: We observed CR isolates exhibited a high frequency of HR, which was largely undetected by standard AST, and correlated with all-cause mortality in the CREDIBLE-CR study (Table). Carbapenem-susceptible isolates exhibited no or low rates of cefiderocol HR (Table). Cephalosporin-resistant bacteria mostly exhibited increased rates of cefiderocol HR, but below those of CR strains. These differences in rates of cefiderocol HR correlated with the mortality data from the APEKS-NP and CREDIBLE-CR trials, across the bacterial species tested (Table). Table: Surveillance rates of cefiderocol heteroresistance correlate with all-cause mortality in the APEKS-NP and CREDIBLE-CR trials Conclusion: These data suggest that the lower rates of cefiderocol HR in carbapenem-susceptible isolates that predominated the APEKS-NP trial may explain the enhanced efficacy of the drug in that study as compared to the CREDIBLE-CR trial. Importantly, the widespread, undetected cefiderocol HR observed among CR pathogens may explain the discordance between this drug's excellent in vitro susceptibility profile and increased patient mortality in the CREDIBLE-CR trial. Disclosures: All Authors : No reported disclosures